Role of mucin 2 gene for growth in Anas platyrhynchos: a novel report - Kumar Murmu, Anuj; Pal, Aruna; Debnath, Manti; Chakraborty, Argha; Pal, Subhamoy; Banerjee, Samiddha; Pal, Abantika; Ghosh, Nilotpal; Karmakar, Utpal; Samanta, Rajarshi (Frontiers in Veterinary Science, 2023)
The Mucin gene is expressed in the mucous membrane of the inner layer of the internal organs. Intestinal mucin 2 (MUC2), a major gel-forming mucin, represents a primary barrier component of mucus layers. This is the first report on the role of mucin genes in growth traits in animals. In the current study, we randomly studied Bengal ducks (Anas platyrynchos) reared from day-old to 10 weeks of age under an organized farm and studied the growth parameters as well as body weight and average daily body weight gain. We characterized the mucin gene for Bengal ducks and observed glycosylation and EGF1 (EGF-like domain signature) as important domains for growth traits in ducks. We observed a better expression profile for the mucin gene in high-growing ducks in comparison to that of lower-growing ducks with real-time PCR. Hence mucin gene may be employed as a marker for growth traits.